Misinterpretation and the meaning of signs in Old English poetry - Bailey, H (2015)
This thesis investigates how Old English poets understood the processes of signification and interpretation through analysis of depictions of poor interpreters and the use of 'sign terms' such as tacen and beacen in the longer Old English poems. The first chapter deals with the Beowulf Manuscript, the second and third chapters consider Elene and Andreas within the network of related poems found in the Vercelli Book and the begin- ning of the Exeter Book, the fourth chapter is on the Junius Manuscript, and the conclusion looks at the use of the 'bright sign' motif across all four major poetic codices. I suggest that there is a 'heroic sign-bearing interpreter’ character-type which several of the poems utilize or ironically invert, and that poor interpretation is nearly always asso- ciated with hesitation, which often resembles acedia. I also argue that there is greater nuance in the poems' depictions of modes of understanding than has previously been acknowledged: Eve in Genesis B does not stand for the senses which subvert the mind, but rather models the limits of rational thought as a means of understanding God, and Elene does not depict a simple opposition of letter and spirit, but a threefold mental pro- cess of learning about the Cross with analogues in exegesis and Augustine's Trinity of the Soul. Finally, I argue that there is a 'bright sign' motif which functions within a brightness-sign-covenant concept cluster, whose evocation as a traditional poetic unit is not identical to the denotation and connotation of its constituent parts. These strands of inquiry taken together demonstrate how Old English poems invest signs with signifi- cance by tapping into a specifically poetic network of allusion.